Human Tyrosyl-DNA Phosphodiesterase 1 Possesses Transphosphooligonucleotidation Activity With Primary Alcohols - Nadezhda Dyrkheeva (Frontiers in Cell and Developmental Biology, 2020)
Human tyrosyl-DNA phosphodiesterase 1 (TDP1) belongs to the phospholipase D superfamily, whose members contain paired catalytic histidine and lysine residues within two conserved motifs and hydrolyze phosphodiester bonds. TDP1 is a DNA repair enzyme that processes 3′ DNA end blocking lesions and a wide range of synthetic DNA adducts as a substrate. TDP1 hydrolyzes DNA-adducts via two coordinated SN2 nucleophilic attacks mediated by the action of two histidine residues and leads to the formation of the covalent intermediate. Hydrolysis of this intermediate is proposed to be carried out by a water molecule that is activated by the His493 residue acting as a general base. It was known that phospholipase D enzymes are able to catalyze not only hydrolysis but also a transphosphatidylation reaction in the presence of primary alcohols in which they transfer the substrate to the alcohol instead of water. Here, we first demonstrated that TDP1 is able to undergo a “transphosphooligonucleotidation” reaction, transferring the substrate residue to the alcohol, thus inducing the formation of covalent DNA adducts with different primary alcohol residues. Such adducts can be accumulated in the conditions of high concentration of alcohol. We demonstrated that glycerol residue was efficiently cleaved from the 3′-end by TDP1 but not by its mutant form associated with the disease spinocerebellar ataxia with axonal neuropathy. Therefore, the second reaction step can be carried out not only by a water molecule but also by the other small nucleophilic molecules, e.g., glycerol and ethanol. Thus, in some cases, TDP1 can be regarded not only as a repair enzyme but also as a source of DNA damage especially in the case of mutation. Such damages can make a negative contribution to the stability of cell vitality.